Factional Journalism in South Africa's Privately Owned Print Media: An Exploration - Matsilele, Trust; Hlungwani, Trevor (The Journal of communication inquiry, 2026)
This paper theorized the concept of “factional journalism” and media capture within South Africa's privately owned print media landscape. This theorization attemps to understand media capture along partisan and factional cleavages in the post democractic dispensation. To understand the factional journalism phenomena in South Africa, we employ a case study design that relies on interviews with Media24 and Independent News and Media (also known as Independent Media) aligned political editors and journalists who have covered the Jacob Zuma and Cyril Ramaphosa's presidencies. Theoretically, we rely on the political economy framework of the media. For this investigation, we wanted to understand how, if at all, media ownership structures and political-economic interests influence journalistic bias in how the Zuma and Ramaphosa presidencies are/have been represented. Findings from this study confirmed the enduring political and business pressures exerted on journalists when covering political elites. While our study observed few cases of outliers, the general trend confirms the continued relevance of the political economy framework as a viable model when seeking to understand editorial bias when covering political elites.